2021
DOI: 10.1183/23120541.00191-2021
|View full text |Cite
|
Sign up to set email alerts
|

An adjusted and time-saving method to measure collateral ventilation with Chartis

Abstract: IntroductionBronchoscopic lung volume reduction with endobronchial valves is an important treatment option in selected patients with severe emphysema and absence of collateral ventilation (CV) in the treatment target lobe. The Chartis system provides an important physiological assessment of the presence or absence of collateral ventilation. We aimed to evaluate a new feature and determine whether low flow during a Chartis measurement is predictive for the absence of collateral ventilation, and whether this all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Newer Chartis ® consoles also show a VT20 trend (flow trend of the last 20 s). Recent studies suggest that if the VT20 reaches 6 mL, CV is not present and the Chartis ® assessment can be stopped, thereby reducing the measurement time by 60 s [38].…”
Section: B Technical Aspectsmentioning
confidence: 99%
“…Newer Chartis ® consoles also show a VT20 trend (flow trend of the last 20 s). Recent studies suggest that if the VT20 reaches 6 mL, CV is not present and the Chartis ® assessment can be stopped, thereby reducing the measurement time by 60 s [38].…”
Section: B Technical Aspectsmentioning
confidence: 99%
“…We validated the VT20 in a recent study showing that all CV negative patients reached a threshold of VT20 ≤6 mL, whereas all CV positive patients reached a VT20 ≥7 mL. 26 In patients measured with conscious sedation, a diagnostic algorithm has been proposed including measurement time, resistance, and expired volume to help interpret the Chartis measurement easier. 27…”
Section: Treatment Options For Emphysemamentioning
confidence: 99%
“…We validated the VT20 in a recent study showing that all CV negative patients reached a threshold of VT20 6 mL, whereas all CV positive patients reached a VT20 !7 mL. 26 In patients measured with conscious sedation, a diagnostic algorithm has been proposed including measurement time, resistance, and expired volume to help interpret the Chartis measurement easier. 27 In case of homogeneous emphysema distribution, low diffusing capacity or lower emphysema destruction scores, the Chartis measurement can also be used to assess the contribution of the target lobe to the total gas-exchange.…”
Section: Chartismentioning
confidence: 99%
“…Notable, a recent study showed that changes in ventilation mode did not affect Chartis outcome [10]. The study protocol described by Koster et al was applied and for analysis, only conclusive Chartis assessments (CV+ and CV) were included in this study [11]. Chartis assessments were recorded with the latest console and software version 6.1.1, which included the VT20 feature.…”
mentioning
confidence: 99%